Competency Management in the Public Sector - Horton, S,Hondeghem, A,Farnham, D (IOS Press, 2002)
Designed for both practitioners and academics, this work seeks to inform the reader about the practice of competency management services in the public sector. It throws light on the origins and meanings of the concept and traces the competency movement from the 1980s in the UK and USA. Cover – Title page – Contents – A. The Competency Movement – Definitions and concepts – The emergence of the competency movement – Assessment – B. Added Value in Human Resources Management: An Analysis of the Competency Management Process – Human resources management and added values – The process of competency development across different organisational levels – Conclusions – 1. HRM Competency Frameworks in the British Civil Service – Background – The survey – A competency framework for the senior civil service – Evaluating old and new competency frameworks – Discussion – 2. Competency Management in Belgium: The Flemish and Federal Governments on the Move – Competency management in the Flemish administration – Federal government: the Copernican revolution – Discussion – 3. Competency-based Management in the Dutch Senior Public Service – The Dutch senior public service – Competencies – Implementation and applications of the SPS competencies – Competency-based management in the SPS: Today and tomorrow – Appendix: All 42 behavioural aspects of SPS competencies – 4. Competency Assessment in Finnish Higher Education – Academic competencies – Academic competency assessment – Case study: assessing academic competencies in the University of Helsinki – Discussion – 5. The Competency Dimension of Leadership: A Study of Top Managers in Swedish Public Administration – Leadership – Concepts and theoretical frameworks – A study of top managers in the Swedish public administration – Discussion – 6. Modest Beginnings for Competency Management in German Public Services: Developing Competencies for already Competent Lawyers? – The exceptional situation of the German public sector – New competencies for the modernisers in the German public sector – Competency management in the state of Schleswig-Holstein – Conclusion.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Civil service; Management by objectives; Administrative agencies; Strategic planning; Administrative agencies; European Union countries; Personnel management; Case studies; Civil service; European Union countries; Personnel management; Case studies; Management by objectives; European Union countries; Case studies; Strategic planning; European Union countries; Case studies; Electronic books